Out of the Crazywoods - Savageau, Cheryl, 1950- (American Indian lives, 2020)
"Out of the Crazywoods is the insightful and riveting story of Abenaki poet Cheryl Savageau's late-life diagnosis of manic depression (also known as bipolar disorder) and her personal journey towards the acceptance and management of this life-long illness to achieve emotional stability"--